2011
DOI: 10.1007/s00464-011-1822-y
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic Dor versus Toupet fundoplication following Heller myotomy for achalasia: results of a multicenter, prospective, randomized-controlled trial

Abstract: Laparoscopic Heller myotomy provides significant improvement in dysphagia and regurgitation symptoms in achalasia patients regardless of the type of partial fundoplication. Although a higher percentage of patients in the Dor group had abnormal 24-h pH test results compared to those of patients who underwent Toupet, the differences were not statistically significant.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
115
0
17

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 278 publications
(135 citation statements)
references
References 29 publications
(39 reference statements)
3
115
0
17
Order By: Relevance
“…The preferred method has been the laparoscopic approach, or laparoscopic Heller myotomy (LHM), due to decreased morbidity and faster recovery [31,32]. Though this method effectively relieves the obstruction, it also increases the risk of gastroesophageal reflux, and most surgeons incorporate an anti-reflux procedure by way of a partial fundoplication [33,34]. Studies initially showed superiority of surgical myotomy in terms of efficiency and durability compared to single balloon dilatation [35,36].…”
Section: Treatmentmentioning
confidence: 99%
“…The preferred method has been the laparoscopic approach, or laparoscopic Heller myotomy (LHM), due to decreased morbidity and faster recovery [31,32]. Though this method effectively relieves the obstruction, it also increases the risk of gastroesophageal reflux, and most surgeons incorporate an anti-reflux procedure by way of a partial fundoplication [33,34]. Studies initially showed superiority of surgical myotomy in terms of efficiency and durability compared to single balloon dilatation [35,36].…”
Section: Treatmentmentioning
confidence: 99%
“…It should be noted that the fundoplication of Dor or Toupet performed in conjunction with a laparoscopic Heller myotomy in patients with achalasia has modest efficacy. High-quality studies of laparoscopy centers have shown that 18-42% of patients present abnormal exposure to the acid in the postoperative period, similar to that observed in the post-POEM study (13,14). It is not clear why the rate of GERD after POEM is not substantially greater than after a Heller myotomy combined with fundoplication.…”
Section: Reflux Disease (Gerd) and Poemmentioning
confidence: 86%
“…Hasta la fecha, solo cuatro series han presentado datos sustanciales sobre la evaluación de la ERGE en sus pacientes utilizando los tres métodos (evaluación sistemática de los síntomas, evaluación endoscópica y estudio ambulatorio de pH) 18,19 . Estos estudios hallaron que el 27-59% de los pacientes tenía signos endoscópicos de reflujo (principalmente esofagitis leve clase A o B de Los Ángeles), el 29-38% tenía anormalmente elevada la exposición al ácido en los estudios de pH y el 15-23% tenían los síntomas frecuentes de reflujo gastroesofágico 20,21 . Estos pacientes han sido tratados eficazmente con IBP.…”
Section: El Poem Y La Enfermedad Por Reflujo Gastroesofágicounclassified